Pictoplasma / : the character compendium. - Thaler, Peter, ....- (Berlin : Pictoplasma, 2012)
The long sought after original is back: After the best-selling Character Encyclopaedia from 2006, Pictoplasma finally presents a brand new compilation with the latest works by the international protagonists and new talents in the field of character design. From illustration and graphic design to fine and urban arts, toys and costumes, this is the unique sourcebook for anyone creative and seeking inspiration. Featuring more than 900 outstanding artworks and individual characters by 200 international artists, The Character Compendium is one of its kind, giving insight to the current trends in figurative design. The Character Compendium features work by Raymond Lemstra, Julia Pott, FriendsWithYou, Florentijn Hofman, Amanda Visell, Brock Davis, Jordan Metcalf, Phunk Studio, Noferin, Nathan Jurevicius, McBess, Koralie and many, many more.